VALORIZATION OF KINNOW FRUIT WASTES - SUSTAINABLE APPROACH TOWARDS ENVIRONMENT - yadav, Kavita; Chahar, Jagmehander; Choudhary, Ambika; Kumar, Manish (Food and Feed Research, 2025)
During the processing of kinnow into juice, around 30-34% of the fruit peel and an average of 20–25 seeds are generated as trash. Consequently, the present study aims to determine the elemental composition, proximate, and oil content of locally cultivated kinnow seed and peel. Kinnow peel essential oil was extracted by hydrodistillation, whereas seed oil was cold-pressed. Characterisation of both extracted oils was performed by FT-IR and GC-MS. The proximate analysis of kinnow seeds powder revealed that it contained proteins, fat, fibres, ash, moisture and carbohydrates in amounts of 13.00±0.32%, 28.65±1.06%, 6±1.28%, 4.771±0.90%, 14.63%, and 31.96 ±  1.10, respectively. The smoke point of kinnow seed oil was 148 °C, and pH, acid value, peroxide value, iodine value, refractive index, saponification value, and unsaponification matter were: 6.26 ±  0.01, 1.125 ±  0.02, 5.91 ±  0.64, 92.56 ± 1.08,1.46 ±  0.002, 187.2 ±  1.73, and 0.51 ±  0.17, respectively.  Moisture content, crude fat, and ash of fresh kinnow peel were found to be 75.08%, 1.27%, and 2.77%, respectively. The water retention capacity (WRC), oil retention capacity (ORC), swelling index, and solubility of dried peel were 6.96g w/g DM, 3.22g oil/g DM, 22.90 ml water/g DM and 36.05% respectively. GC-MS revealed hexadecenoic acid was the most common saturated fatty acid in kinnow seed oil, with an area of 24.28% and retention time 35.9 min, followed by esconic acid with 1.12% area, 42.1 min retention time and stearic acid with an area of 6.59%, retention time 38.8 min. The most abundant compound in peel essential oil was D-Limonene, with a retention time of 7.42 min as identified by GC-MS.